Evaluation of Antioxidant Activity and Radical Scavenging Capacities of Different Fractions of Nepeta hindostana - Zahid Qurashi, Muhammad; Riaz*, Sadaf; Akhtar Qurashi, Naveeda; Ullah Khan, Islam (Asian Journal of Chemistry, 2011)
The aim of this research is to study the in vitro antioxidant and radical scavenging activity of Nepeta hindostana components which are effective against different disorders like cardiovascular and kidney diseases. These are the traditionally used herbs against degenerative diseases so it is an important task to evaluate their antioxidant activity. The herb was extracted in aqueous as well as in different organic solvents. Antioxidant potential and radical scavenging activity of the seven fractions were investigated by using different antioxidant assays such as {2,2´-azinobis(3-ethylbenzothiazoline-6-sulphonic acid)}, ferric reducing antioxidant power, total phenolic contents and diphenyl-1-picrylhydrazyl radical scavenging assay. Trolox equivalent antioxidant activity of the aqueous and organic fraction of these herbs was determined by calculating the % inhibition of the coloured radical solution after reaction with sample and standard antioxidants by comparing with the standard curve formed by Trolox as standard antioxidant. Total phenolic contents and ferric reducing antioxidant power decolourization assays, showed a wide range of antioxidant activity. Using total phenolic content assay the amount of total phenolics components ranged from 0.294 to 7.872 μM and Ferric reducing antioxidant power ranged from 1.032 to 7.906 μM which showed the presence of many phenolic components in its composition. On the basis of such antidisease activity of these herbs attributes the presence of these antioxidant components.